2014
DOI: 10.1159/000358599
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Responders to Sorafenib in Hepatocellular Carcinoma: Is Tumor Volume Measurement the Way Forward?

Abstract: Objectives: Early assessment of hepatocellular carcinoma (HCC) response during sorafenib (SO) treatment is challenging, since tumor necrosis, extension and radiological appearance can be inhomogeneous. We evaluated the predictive value of different imaging criteria - such as Response Evaluation Criteria in Solid Tumors (RECIST) 1.1, European Association for the Study of the Liver (EASL), modified RECIST (mRECIST), tumor density and volume variations - in the early follow-up of SO treatment. Methods: The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
1
13
0
1
Order By: Relevance
“…RECIST 1.1‐based radiological assessment is used widely for treatment response classification and as a surrogate end‐point both in clinical trials and in routine practice. However, the development of molecular targeted therapies to lessen tumor vascularity has shown that the RECIST 1.1 assessment has limitations . Some modifications to RECIST 1.1 for HCC treatment have been proposed, including mRECIST, EASL, and the Choi criteria, which are considered to better reflect treatment effects .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RECIST 1.1‐based radiological assessment is used widely for treatment response classification and as a surrogate end‐point both in clinical trials and in routine practice. However, the development of molecular targeted therapies to lessen tumor vascularity has shown that the RECIST 1.1 assessment has limitations . Some modifications to RECIST 1.1 for HCC treatment have been proposed, including mRECIST, EASL, and the Choi criteria, which are considered to better reflect treatment effects .…”
Section: Discussionmentioning
confidence: 99%
“…However, the development of molecular targeted therapies to lessen tumor vascularity has shown that the RECIST 1.1 assessment has limitations. 7,9,17,21 Some modifications to RECIST 1.1 for HCC treatment have been proposed, including mRECIST, EASL, and the Choi criteria, which are considered to better reflect treatment effects. 9 However, these modifications are still based on a unidimensional manual assessment and are strongly affected by heterogeneities in tumor appearance, that is, CT enhancement pattern, induced by sorafenib and other locoregional therapies such as radiofrequency ablation (RFA) and transcatheter arterial chemoembolization (TACE).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to recently published studies focused on HCC patients, a 10% increase in volume rate after two months of therapy correlates with a poor prognosis[80,81]. The role of MR diffusion weighted imaging has also been investigated in response assessment.…”
Section: Imaging Studies In Prediction and Evaluation Of Response To mentioning
confidence: 99%
“…There are several standard oncological methods for assessing tumor treatment response such as monitoring for decreases in alpha fetoprotein (AFP) [12], and different criteria have been put forth by liver societies: Response Evaluation Criteria in Solid Tumors (RECIST) 1.1, European Association for the Study of the Liver (EASL), modified RECIST (mRECIST), and Choi's criteria, which monitors change in tumor density and arterial-enhancing tumor volume variations. These methods for assessing tumor response were compared in sorafenib-treated patients (n=22), showing that response criteria and volume measurements were reproducible (k> 0.80).…”
Section: Assessment Of Hcc Treatmentmentioning
confidence: 99%